Anna Karenina - Tolstoy, Leo graf 1828-1910 (Penguin Books USA Inc., 1961)
Tolstoy's classic tale of love and adultery set against the backdrop of high society in Moscow and Saint Petersburg. A rich and complex masterpiece, the novel charts the disastrous course of a love affair between Anna, a beautiful married woman, and Count Vronsky, a wealthy army officer.